Edukasi Mitigasi Bahaya Kebakaran Akibat Arus Pendek melalui Standarisasi Instalasi Listrik Rumah Tangga - Yunita Subarwanti; Willy Artanika Rikarda; Frendi Maulana; Matsna Nurul Kholidah; Chairil Very Aziz; Muhamad Doni Andrianto (Universitas Pahlawan Tuanku Tambusai, 2026)
Household electrical installations that do not comply with safety standards remain one of the leading causes of fires due to electrical short curcuits in residential areas. Limited public knowledge of electrical installation standards and the importance of protection systems highlights the need for educational programs. This community service program aimed to improve community knowledge and awareness of fire hazard mitigation through education on standardized household electrical installations based PUIL 2011. The program was conducted on May 19, 2026, in Tegal Yoso Village and involved 20 participants. The Participatory Technology Development approach was implemented through lectures, discussions, demonstrations, hands-on practice, and evaluation using pre-test and post-test. The results showed an increase in participants’ average knowledge score from 42.1% to 92.1%. Participants demonstrated improved understanding of the functions of MCB, grounding systems, SNI-compliant electrical materials, and fire prevention measures. These findings indicate that practice-based education effectively improves community literacy on electrical safety.